APPLICATION AND SIGNIFICANCE OF THE VIDEO GAME LOCALIZATION PROCESS - Rea Tot; Ivan Dunđer (Elektronički Zbornik Radova Veleučilišta u Šibeniku)
With the rapid development and great growth in popularity of video games, the video game industry has undergone a significant process of globalization in recent years. Video games are an essential factor in the digital entertainment industry today and attract many players, regardless of gender, age, social, political or economic status. This popularity and rapid development of video games is leading to the growing need for companies to make their video games available to as many people as possible in order to achieve a high return on fi nancial investments. Therefore, there is an obvious desire and need for video games to be tailored to all potential users, wherever they are. This is an extremely important factor in player satisfaction, and as such is very important in overcoming the language barrier, promoting the company’s international image and achieving good business results. But this means that the video game needs to be adapted to a large number of languages, cultural diff erences, ways of speaking and thinking, and at the same time to remove everything that is not suitable for the target market. One of the possible solutions for adapting to the international market is certainly localization, the application of which seeks to meet the needs of all players and markets. Video games, however, have specific features that distinguish them from other media, as they focus on player interactions and graphic elements of a game, which is unique compared to translating a novel or film. This paper provides an overview of video game adaptation strategies and the characteristics of the adaptation flow, with special emphasis on the localization approach as well as problems and open issues in the process of adapting video games to the international market.